2012
DOI: 10.1289/ehp.1003378
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and Postnatal Arsenic Exposure and Body Size to 2 Years of Age: A Cohort Study in Rural Bangladesh

Abstract: Background: Exposure to arsenic via drinking water has been associated with adverse pregnancy outcomes and infant morbidity and mortality. Little is known, however, about the effects of arsenic on child growth.Objective: We assessed potential effects of early-life arsenic exposure on weight and length of children from birth to 2 years of age.Methods: We followed 2,372 infants born in a population-based intervention trial in rural Bangladesh. Exposure was assessed by arsenic concentrations in urine (U-As) of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 29 publications
2
47
0
1
Order By: Relevance
“…Chronic exposure is linked to skin, bladder, lung, liver and kidney carcinogenesis as well as skin hyperkeratoses, and cardiovascular and immunological effects [National Research Council (US) Subcommittee on Arsenic in Drinking Water, 2001]. Prenatal arsenic exposures, in some cases at low levels of exposure, have been linked to reduced birth weight (Cnattingius, 2004;Guan et al, 2012;Hopenhayn et al, 2003;Huyck et al, 2007;Llanos and Ronco, 2009;Rahman et al, 2009;Xu et al, 2011;Yang et al, 2003) although other studies have not observed this association (Kwok et al, 2006;Saha et al, 2012), or have linked exposure to spontaneous abortion or neonatal death, thereby eliminating more subtle effects at birth (Myers et al, 2010;Sohel et al, 2010). Although the overt phenotypes resulting from arsenic exposure are well documented, the mechanistic basis of its toxicity remains unclear, as this metalloid is not overtly genotoxic.…”
Section: Dna Methylationmentioning
confidence: 99%
“…Chronic exposure is linked to skin, bladder, lung, liver and kidney carcinogenesis as well as skin hyperkeratoses, and cardiovascular and immunological effects [National Research Council (US) Subcommittee on Arsenic in Drinking Water, 2001]. Prenatal arsenic exposures, in some cases at low levels of exposure, have been linked to reduced birth weight (Cnattingius, 2004;Guan et al, 2012;Hopenhayn et al, 2003;Huyck et al, 2007;Llanos and Ronco, 2009;Rahman et al, 2009;Xu et al, 2011;Yang et al, 2003) although other studies have not observed this association (Kwok et al, 2006;Saha et al, 2012), or have linked exposure to spontaneous abortion or neonatal death, thereby eliminating more subtle effects at birth (Myers et al, 2010;Sohel et al, 2010). Although the overt phenotypes resulting from arsenic exposure are well documented, the mechanistic basis of its toxicity remains unclear, as this metalloid is not overtly genotoxic.…”
Section: Dna Methylationmentioning
confidence: 99%
“…A previous study from this mass arsenic poisoning already reported lower height among exposed victims at adolescence, although details were not provided (Uehata et al 1977). In addition, a prospective cohort study from Bangladesh suggested an inverse association between early-life exposure to arsenic and height at infancy (Gardner et al 2013;Saha et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from neurotoxicity, evidence on long-term effects of developmental toxicity of arsenic is limited (Vahter 2008), but possible adverse effects on birth outcomes include low birth weight (Bloom et al 2014;Gilbert-Diamond et al 2016;Kile et al 2016;Rahman et al 2009). Further, a prospective cohort study from Bangladesh suggests an inverse association between early-life arsenic exposure from contaminated drinking water and children's growth during infancy (Gardner et al 2013;Saha et al 2012). Growth inhibition due to arsenic exposure has been supported by laboratory animal studies that show decreased body length and femur length (Hu et al 2012), as well as decreased bone mass density (Wu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…NCC give rise to rib cage (Henderson et al, 1999); (1) (Grandjean et al, 1997); (2) (Grandjean and Landrigan, 2006); (3) (Opler et al, 2008); (4) (Ha et al, 2009); (5) (Tian et al, 2009); (6) (Kippler et al, 2012); (7) (Hamadani et al, 2011); (8) (Saha et al, 2012); (9) (Eubig et al, 2010); (10) (Patandin et al, 1999); (11) (Valvi et al, 2012); (12) (Lai et al, 2002); (13) (Chen et al, 1992); (14) (Zarn et al, 2004); (15) (Di Renzo et al, 2007); (16) (Machera, 1995); (17) (Giavini and Menegola, 2010); (18) (Krieger, 2004); (19) (Dean et al, 2002); (20) (Arndt et al, 2005); (21) (Meador et al, 2006); (22) (Rasalam et al, 2005); (23) (Menegola et al, 2005b); (24) (Verbois, 2006); (25) (Valenzuela-Fernandez et al, 2008).…”
Section: Biostatistics and Data Display Algorithmsunclassified